Accelerating S/4HANA Migrations through Strategic Enterprise Architecture - Ramesh Mahankali, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Enterprise architecture is pivotal in orchestrating successful SAP S/4HANA migrations, yet many organizations struggle to leverage architectural principles effectively throughout their transformation journey. This article examines how enterprise architects can accelerate S/4HANA migrations by integrating established frameworks like TOGAF with SAP's Active methodology while maintaining architectural governance and business continuity. This article presents a comprehensive architectural approach that addresses key challenges in data migration, legacy system integration, and cloud infrastructure optimization by analyzing real-world implementations and industry best practices. This article draws from a detailed case study of a global manufacturing company's successful migration, highlighting how strategic architectural decisions reduced migration time by 40% and minimized business disruption. Special attention is given to emerging patterns in hybrid cloud deployments, automated testing frameworks, and data quality management that have proven crucial for migration success. This article provides enterprise architects and technical leaders with practical insights for developing robust migration strategies that balance immediate technical requirements with long-term organizational objectives, ultimately accelerating their journey to S/4HANA while maintaining architectural integrity.
Keywords: Enterprise Architecture; S/4HANA Migration; TOGAF Integration; Digital Transformation; Cloud Infrastructure